Basin Development Challenges - Stakeholder Consultation Workshop Report - Volta River Basin - Schuetz, Tonya; Douthwaite, Boru; Nguyen Khoa, Sophie; Vidal, Alain (CGIAR Challenge Program on Water and Food, 2009)
The overall objective of this workshop was to consult key stakeholders knowledgeable about the proposed Volta BDC on how research can best contribute to tackling the BDC. In the Volta, the proposed BDC was “Rainwater management and small reservoirs in Northern Ghana and Burkina Faso”. A brief description of the proposed BDC, taken from the CPWF’s 2010 – 2013 Medium Term Plan, was sent to orientate the participants before the workshop (see Annex 1). Participants were invited to the workshop to provide advice on how research can best contribute to the BDC, thus helping the CPWF Management Team design the BDC research program (Step 3 in Table 1). The specific objectives are shown in Figure 1 together with the process that was followed to achieve them. The process used elements of Participatory Impact Pathway Analysis (PIPA)1 and incorporated lessons learned in conducting similar consultations in other basins.